STUDY THE EFFECT OF LONGITUDINAL TAPERED FINS AND PINNED FINS IN A VERTICAL DUCT ON COOLING SURFACE TEMPERATURE - MOHSEN, OSAMA A.; AL-KUBAISI, OMAR; SALIH, SUHA M.; HATHAL, MUSTAFA M.; MAHUOF , AYAD AIED (Journal of Duhok University, 2023)
Heat is dissipated to the environment through heat sinks in electronic parts and fins in internal combustion engines, the extended surface plays a significant role in the heat transfer of many heat generation devices. Depending on the generation source, the extended surface can be used for cooling or heating. In the present study, three types of plates are used in vertical ducts (flat plate, tapered fin, and pinned fin heat sink) under differing power inputs (10 to 60 W) and varying air velocities, from 0 m/s for natural convection to 0.5–2.5 m/s for forced convection. Then study the temperature difference with the distance of the fins from the back plate. The experimental result shows a good temperature difference when we use tapered fins more than pinned fins, which in turn gives a lower temperature difference than the flat plate. Also, temperature will decrease when far from the back plate for the fin.